1984
DOI: 10.1084/jem.159.3.679
|View full text |Cite
|
Sign up to set email alerts
|

Studies of hematopoietic stem cells spared by 5-fluorouracil.

Abstract: Mouse marrow cells were exposed to 5-fluorouracil (FU) either in vivo or in vitro and the effects on the hematopoietic stem cell compartment were studied. The drug was highly toxic to bone marrow cells including the spleen colony-forming unit (CFU-S) population. The small population of stem cells surviving FU, however, caused a different pattern of spleen colony growth when injected into lethally irradiated mice. Whereas numbers of spleen colonies caused by normal marrow cells remained constant during an 8-14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
0

Year Published

1985
1985
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(77 citation statements)
references
References 16 publications
2
75
0
Order By: Relevance
“…This suggests that HSCs are spared, and that sublethal irradiation may be useful for enriching stem cell subsets akin to the use of 5-fluorouracil treatment in mice. 27,28 The response to sublethal irradiation may also be useful for genetic screens designed to uncover functional defects in the repopulation of blood cells by HSCs. Since spermatogonial progenitors are also transiently ablated in the testis, abnormal repopulation of this organ could simultaneously be assessed to find stem cell mutations in the male germ line.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that HSCs are spared, and that sublethal irradiation may be useful for enriching stem cell subsets akin to the use of 5-fluorouracil treatment in mice. 27,28 The response to sublethal irradiation may also be useful for genetic screens designed to uncover functional defects in the repopulation of blood cells by HSCs. Since spermatogonial progenitors are also transiently ablated in the testis, abnormal repopulation of this organ could simultaneously be assessed to find stem cell mutations in the male germ line.…”
Section: Discussionmentioning
confidence: 99%
“…This is important because the following theories all imply that the HSC compartment is heterogeneous: that HSC reside in niches that influence their self-replication (151, that microenvironments direct their differentiation (61, that HSC are characterized by an age structure (181, that HSC generate CFU-S through a marrow-dependent maturational step (24), and that HSC maintain normal hematopoiesis through clonal selection (14). These theories could be directly tested if HSC with different phenotypes could be isolated.…”
Section: Fluorescence (Log)mentioning
confidence: 99%
“…To facilitate the enrichment of CFU-B 1, a number of physical and immunological characteristics ofthese cells could be utilized (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Another means of obtaining enriched populations of CFU-BI might be to pharmacologically purge the marrow of more differentiated elements by in vitro exposure to chemotherapeutic agents (29,30). Van Zant has previously shown that in vitro exposure of murine marrow cells to 5-fluorouracil (5-FU) results in the direct, rapid kill of more differentiated progenitor cells and the selective sparing of primitive pluripotent hematopoietic stem cells (30).…”
Section: Introductionmentioning
confidence: 99%
“…Another means of obtaining enriched populations of CFU-BI might be to pharmacologically purge the marrow of more differentiated elements by in vitro exposure to chemotherapeutic agents (29,30). Van Zant has previously shown that in vitro exposure of murine marrow cells to 5-fluorouracil (5-FU) results in the direct, rapid kill of more differentiated progenitor cells and the selective sparing of primitive pluripotent hematopoietic stem cells (30). 5-FU does not require in vivo metabolism for this effect to occur.…”
Section: Introductionmentioning
confidence: 99%